TRANSLATION OF ARCHAISMS IN ENGLISH CONTRACTUAL DOCUMENTS - Listyo, Indra; Laksman-Huntley, Myrna; Dewi, Haru Deliana (UI Scholars Hub, 2024)
This research investigates the translation of archaisms, particularly here-words and there-words, from English to Indonesian, highlighting the unique challenges they present. Using a descriptive qualitative method, the study is framed by the Skopos theory and ISO 24495-1:2023 - Plain Language principles. The Skopos theory stresses the translation's intended purpose, advocating a functional approach that enhances the target text's communicative efficacy. ISO 24495-1:2023 ensures legal documents are clear, concise, and accessible, maintaining their legal integrity. The research examines a bilingual English-Indonesian contractual document, the Global Master Repurchase Agreement, to analyze the translation of these archaic terms. Findings show that translating archaisms demands careful attention to nuances, cultural connotations, and legal implications. The study reveals that using plain Indonesian expressions improves readability and reduces misinterpretation. Emphasizing cultural and contextual considerations, it advocates for strategies that maintain the original text's legal validity while enhancing accessibility. This aligns with the global movement towards plain language in legal documents, promoting transparency and efficiency in international transactions. The research provides insights into effective translation practices for legal archaisms, supporting the development of clearer legal documentation in Indonesia and contributing to the broader discourse on improving legal translation in a globalized world.